Challenges and opportunities for sarcoma care and research in Latin America: a position paper from the LACOG sarcoma group - Pestana, RC (2024)
As a developing region, Latin America faces unique cancer control and prevention challenges, which are intensified when considering rare cancers, including sarcomas. Sarcomas are a group of malignancies that arise in the connective tissues of the body—such as muscle, fat, nerves, blood vessels, and bones—accounting for a diverse range of tumours that, although rare, require specialized attention. Sarcoma care and research in Latin America require a comprehensive approach that includes deeper epidemiologic knowledge, diagnostic capacity building, access to innovative treatments, increased patient advocacy, and strengthening of clinical research capacity. This article will review current challenges and opportunities for treating patients with sarcoma in Latin America and outline a pathway toward improvement for regional collaborative groups.